(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2022)
The publication reveals the religious worldview determinants, which at the categorical and conceptual level are expressed by sacred vocabulary, functional in the Ukrainian historical novel by Lina Kostenko “Berestechko”, which represents the background biblical knowledge about the described historical epoch. Artistic photographic comparison of the modern (historical commentary and assessment of the consequences of the Battle of Berestechko, analysis by historians of the campaign led by Bohdan Khmelnytsky from the standpoint of further development of the state) and the experience of sacredness creates the aesthetics of modern Ukrainian historical novel. The plot of the historical novel, according to the writer, is based on understanding the failed campaign of Bohdan Khmelnytsky near Berestechko (1651): the reasons for the defeat of the Cossack army, the nature of the betrayal, reflections on the future of the state for further socio-political progress of the state. The author uses the technique of artistic reflection, which reveals as deeply as possible the course of cognitive-affective states of the leader. A feature of the historical novel is the pervasive sacred context. The protagonist is active in a monologue, a dialogue with the soul, God, uses sacred concepts (sacred person, God-pleasing action / deed, sacred object, sacred place, sacred time) during the development of reflection. Lina Kostenko uses inherent expressions for the realization of the creative idea, the adregent interpretation of which actualizes issues related to the history of Ukraine, reveals the compared historical events as a background context. Structural and semantic analysis of the language material allowed to distinguish the following religious correlations, expressed by sacred vocabulary: Messiah / Hetman (piety, justice, devotion to the Fatherland); man (sin / charitable behavior); land (Promised Land / Ukraine). Regularities of use of sacred nominations as a part of biblical expressions / onyms, which have additional positive or negative coloring, are established. The contextual load of proper names, which have acquired a generalized meaning (names of hetman’s associates), is considered. The further prospects of research of features of functioning of sacred vocabulary which consist in working out of hermeneutics of adherent / inherent expressions, functional in writing, taking into account the historical commentary are outlined; modeling of figurative dynamics based on linguistic and philosophical analysis.